Status of the Freshwater Mussel Fauna Pendleton Island Mussel Preserve, Clinch River Virginia - Sally D. Dennis (Hello World!, 1989)
During August of 1987, at the request of the Virginia Nature Conservancy, I instituted an evaluation of the freshwater mussel fauna of The Nature Conservancy Preserve in the Clinch River at Pendleton Island (CRM 226), Scott County, Virginia. The purpose of this evaluation was to provide background data which would be useful in monitoring the condition of the mussel fauna of this river reach. While it is the particular aim of the Conservancy to keep track of rare and endangered mussel species inhabiting this preserve, most of these species do not occur in sufficient abundance to allow reliable monitoring of their status. Rare species are not easily sampled quantitatively (Kovalak et al., 1986) and, therefore, population parameters such as age-class structure cannot be determined with any degree of reliability for them. For this reason, a sampling program was designed to evaluate community structure. Changes in percent composition of species and in age-class structure of the more abundant species can. it is hoped, be used to detect changes in habitat quality.